2021
DOI: 10.24996/ijs.2021.62.4.5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Aqueous Extract of the Leaves of the Local Plant Eruca sativa on Lipid Profile and Some Minerals in the Blood of Male White Mice

Abstract: Eruca sativa, commonly known as rocket salad, is a popular vegetable to which a wide range of health benefits are attributed. This study aimed to examine the effects of the aqueous extract of E. sativa leaves on lipid profile and some minerals, such as calcium and magnesium, in blood of male albino mice under normal physiological condition. Two experiments were separately conducted, each with eighteen male albino mice divided into 3 equal groups, which included control, treated group (1), and treated group (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The BMI values for 342 participants were equal to or lower than 18 and those for 99 participants were normal (above 18). The values were in the overweight range (25)(26)(27)(28)(29) for 60 donors and in the obese range for 17 donors (higher than 30). Most participants were underweight (66%).…”
Section: Body Mass Index (Bmi)mentioning
confidence: 91%
See 1 more Smart Citation
“…The BMI values for 342 participants were equal to or lower than 18 and those for 99 participants were normal (above 18). The values were in the overweight range (25)(26)(27)(28)(29) for 60 donors and in the obese range for 17 donors (higher than 30). Most participants were underweight (66%).…”
Section: Body Mass Index (Bmi)mentioning
confidence: 91%
“…However, triglyceride and nutritional status among the Kurdish population are not adequately studied. Malnutrition and nutritional status among Kurdish children were estimated previously [24 -25], indicating that about 16% of Kurdish children were underweight, and recent study estimated the effect of Eruca sativ on the lipid profile among Kurdish peoples inSulaimani Province-Iraq [26]. Triglyceride and cholesterol estimates are medically important in relation to the nutritional status.…”
Section: Introductionmentioning
confidence: 96%
“…Herbs have been used as therapy and in other medicinal uses for thousands of years. Herbal medicines are complex mixtures of about 50 chemical constituents [1,2]. Anise is an aromatic plant which has a long tradition of being used in conventional medicine and pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial, antigenotoxic, antidiuretic, stimulant, stomach disorders analgesic, antioxidant, antiulcer, hepatoprotective activities, antidiabetic, antiacne, antihyperlipidemic, antihyperglycemic, and anti-inflammatory properties have been reported for a variety of phytochemicals found in E. sativa. In Central Asia, E. sativa seed oil, also known as taramira oil or jamba oil, is used for massages, hair treatments, and as an anti-influenza drug (Awadelkareem et al, 2022) .. investigation found that E. sativa had no discernible impact on VLDL levels (Salih, 2018;Weli et al, 2021). "…”
Section: Introductionmentioning
confidence: 99%